The Changing Spatial Distribution of Economic Activity Across U.S. Counties. - Fafchamps, M; Desmet, K (Department of Economics (University of Oxford), 2000)
This paper studies the recent trends in the spatial distribution of economic activity in the United States. Using county-level employment data for 13 sectors - which cover the entire economy - we apply semi-parametric techniques to estimate how agglomeration and congestion effects have changed between 1972 and 1992. Non-service sectors are found to be spreading out and moving away from centers of high economic activity to areas 20 to 60 kilometers away; service sectors, on the contrary, are increasingly concentrating in areas of high economic activity by attracting jobs from the surrounding 20 kilometers.